KEWAJIBAN NOTARIS DALAM MEMBERIKAN JASA HUKUM SECARA CUMA-CUMA KEPADA MASYARAKAT YANG TIDAK MAMPU BERDASARKAN PASAL 37 UUJN DI KOTA PADANG - Novira, Felti; Hasbi, Muhammad; Syofyan, Syofirman (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
Article 37 of the Notary Position Act (UUJN) regulates the obligation of notaries to provide free legal services in the notarial field to underprivileged communities. However, this provision has led to varying interpretations regarding the types of legal services intended, as well as the criteria for identifying individuals as underprivileged. This study aims to examine the types of free legal services that notaries can provide and their implementation in Padang City. The research approach used is empirical-juridical, with data collected through interviews and document studies. The findings show that while UUJN mandates notaries to offer free legal services to the underprivileged, the types of services provided and the criteria for identifying the underprivileged are not clearly defined. Consequently, the implementation of Article 37 of the UUJN in Padang City is interpreted differently by notaries, including offering legal consultations or creating deeds at no cost. This study recommends the need for clearer regulations to ensure legal certainty in the implementation of free legal services by notaries.